Physical properties of the GaPd2 intermetallic catalyst in bulk and nanoparticle morphology. (December 2015) - Wencka, M.; Schwerin, J.; Klanjšek, M.; Krnel, M.; Vrtnik, S.; Koželj, P.; Jelen, A.; Kapun, G.; Jagličić, Z.; Sharafutdinov, I.; Chorkendorff, I.; Gille, P.; et al.
Abstract: Intermetallic compound GaPd2 is a highly selective catalyst material for the semi-hydrogenation of acetylene. We have determined anisotropic electronic, thermal and magnetic properties of a GaPd2 monocrystal along three orthogonal orthorhombic directions of the structure. By using 69 Ga and 71 Ga NMR spectroscopy, we have determined the electric-field-gradient tensor at the Ga site in the unit cell and the Knight shift, which yields the electronic density of states (DOS) at the Fermi energy ε F . The DOS at ε F was determined independently also from the specific heat. To see the change of electronic properties of the GaPd2 phase on going from the bulk material to the nanoparticles morphology, we have synthesized GaPd2 /SiO2 supported nanoparticles and determined their electronic DOS at ε F from the 71 Ga NMR spin-lattice relaxation rate. The electronic DOS of the GaPd2 was also studied theoretically from first principles. All results are compared to the chemically related compound GaPd. The active–site-isolation concept for an increased catalytic selectivity is discussed in relation to the GaPd2 and GaPd structures. Graphical abstract: Highlights: GaPd2 is a highly selective intermetallic catalyst for semi-hydrogenation of alkynes. Physical properties of GaPd2 phase in bulk and nanoparticle morphology are presented. A comparison of the GaPd2 properties to GaPd compound is made. The origin of high catalytic selectivity of GaPd2 and GaPd is discussed.